2019
DOI: 10.1002/cyto.b.21771
|View full text |Cite
|
Sign up to set email alerts
|

L‐Selectin Expression is Influenced by Phosphatase Activity in Chronic Lymphocytic Leukemia

Abstract: Background Adhesion receptors have important role in cellular invasiveness and L‐selectin is a primary determinant in the binding of chronic lymphocytic leukemia (CLL) cells to several glycated proteins on endothelial cells. We investigated L‐selectin expression on CLL cells and explored the mechanisms that lead to their shedding. Methods Surface and soluble L‐selectin expression levels were studied by flow cytometry and immunoassay, respectively. Magnetically isolated B‐cells from patients and controls were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For instance, E-selectin has been shown to be a key receptor in leukemia [ 24 , 25 ], myeloma [ 23 ], as well as in solid tumors such as pancreatic [ 26 , 27 , 28 ], prostate [ 29 , 30 ], colon [ 31 , 32 ] and breast [ 33 , 34 , 35 ] cancer cells. L-selectin has been shown to be a key receptor for chronic lymphocytic leukemia [ 20 , 36 ]. Moreover, P-selectin has been shown to play an important role in myeloma [ 15 , 18 , 22 , 23 ].…”
Section: The Role Of E-selectin In Cancer Pathophysiologymentioning
confidence: 99%
“…For instance, E-selectin has been shown to be a key receptor in leukemia [ 24 , 25 ], myeloma [ 23 ], as well as in solid tumors such as pancreatic [ 26 , 27 , 28 ], prostate [ 29 , 30 ], colon [ 31 , 32 ] and breast [ 33 , 34 , 35 ] cancer cells. L-selectin has been shown to be a key receptor for chronic lymphocytic leukemia [ 20 , 36 ]. Moreover, P-selectin has been shown to play an important role in myeloma [ 15 , 18 , 22 , 23 ].…”
Section: The Role Of E-selectin In Cancer Pathophysiologymentioning
confidence: 99%
“…Peripheral blood neutrophils were homogeneous and express FcγRIII (CD16) and L-selectin (CD62L) within a narrow range, typically characterized as CD16 bright CD62L bright (mature), CD16 dim CD62L bright (immature), CD16 dim CD62L dim (apoptotic) neutrophils ( 22 ). L-selectin(CD62L) can account for impaired rolling and migration ability of leukocytes ( 23 ). The expression of HLA-DR was defined as an activation marker ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The protein tyrosine phosphatase receptor (PTPR) type O Tyr-phosphatase was shown to interfere with CLL progression and survival and was proposed as a tumor suppressor gene (17). Moreover, it was reported that PHLPP1 and phosphatase-2A Ser/Thr-phosphatases are downmodulated in CLL, thus favoring prosurvival signals in CLL (18,19). Moreover, SHIP1 and SHIP2 5-phosphate phosphatases have been shown to interfere with prosurvival signaling mechanisms in CLL (20,21).…”
Section: Activation Of Protein Tyrosine Phosphatase Receptor Type G S...mentioning
confidence: 99%